ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Afriyanti Hasanah (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to analyze the effect of Good Corporate Governance on tax avoidance.This study uses 4 variables for measuring Good Corporate Governance namely Institutional Ownership, Audit Quality, Company Size, and Political Connection. The population of this study are all manufacturing sector companies that have been listed on the Indonesia Stock Exchange (BEI) in the 2013-2017 period with a total final sample of 160 companies that have met the criteria. The samples in this study used nonprobability sampling method with purposive sampling technique in order to get a sample size of 32 companies. Data analysis technique used was simple linear regression analysis of each variable by using Eviews. The results showed that Institutional Ownership did not affect tax avoidance, while Audit Quality, Company Size, and Political Connection had an influence on tax avoidance. Keywords: Tax Avoidance, Institutional ownership, Audit Quality, Company Size, and Political Connection